Protein Hydrolysis by Immobilized and Stabilized Trypsin - Marques, Daniela [UNESP]; Pessela, Benavides C.; Betancor, Lorena; Monti, Rubens [UNESP]; Carrascosa, Alfonso V.; Rocha-Martin, Javier; Guisan, Jose M.; Fernandez-Lorente, Gloria (Wiley-Blackwell, 2011)
The preparation of novel immobilized and stabilized derivatives of trypsin is reported here. The new derivatives preserved 80% of the initial catalytic activity toward synthetic substrates [benzoyl-arginine p-nitroanilide (BAPNA)] and were 50,000-fold more thermally stable than the diluted soluble enzyme in the absence of autolysis. Trypsin was immobilized on highly activated glyoxyl-Sepharose following a two-step immobilization strategy: (a) first, a multipoint covalent immobilization at pH 8.5 that only involves low pK(a) amino groups (e. g., those derived from the activation of trypsin from trypsinogen) is performed and (b) next, an additional alkaline incubation at pH 10 is performed to favor an intense, additional multipoint immobilization between the high concentration of proximate aldehyde groups on the support surface and the high pK(a) amino groups at the enzyme surface region that participated in the first immobilization step. Interestingly, the new, highly stable trypsin derivatives were also much more active in the proteolysis of high molecular weight proteins when compared with a nonstabilized derivative prepared on CNBr-activated Sepharose. In fact, all the proteins contained a cheese whey extract had been completely proteolyzed after 6 h at pH 9 and 50 degrees C, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Under these experimental conditions, the immobilized biocatalysts preserve more than 90% of their initial activity after 20 days. Analysis of the three-dimensional (3D) structure of the best immobilized trypsin derivative showed a surface region containing two amino terminal groups and five lysine (Lys) residues that may be responsible for this novel and interesting immobilization and stabilization. Moreover, this region is relatively far from the active site of the enzyme, which could explain the good results obtained for the hydrolysis of high-molecular weight proteins. (C) 2011 American Institute of Chemical Engineers Biotechnol. Prog., 27: 677-683, 2011
Keywords: cheese whey hydrolysis; two-step multipoint enzyme immobilization; multichain immobilization of trypsin